2013
DOI: 10.1007/s11248-013-9708-5
|View full text |Cite
|
Sign up to set email alerts
|

A threshold level of oxalate oxidase transgene expression reduces Cryphonectria parasitica-induced necrosis in a transgenic American chestnut (Castanea dentata) leaf bioassay

Abstract: American chestnut (Castanea dentata) was transformed with a wheat oxalate oxidase (oxo) gene in an effort to degrade the oxalic acid (OA) secreted by the fungus Cryphonectria parasitica, thus decreasing its virulence. Expression of OxO was examined under two promoters: a strong constitutive promoter, CaMV 35S, and a predominantly vascular promoter, VspB. Oxo gene transcription was quantified by RT-qPCR. Relative expression of OxO varied approximately 200 fold among events produced with the 35S-OxO. The lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 35 publications
2
86
0
Order By: Relevance
“…Because decreased oxalate production in C. parasitica is associated with reduced virulence Anagnostakis 1983, 1985;Chen et al 2010), it was hypothesized that detoxifying oxalate at the canker margins would protect plant cells and enhance resistance to the blight. A natural effect of OxO is to augment host resistance, and numerous studies have shown that overexpressing OxO (i.e., producing more of the enzyme or producing it in additional tissues) in transgenic plants can enhance resistance to a variety of pathogens (Donaldson et al 2001;Liang et al 2001;Schneider et al 2002;Hu et al 2003;Livingstone et al 2005;Dong et al 2008;Walz et al 2008;Partridge-Telenko et al 2011;He et al 2013;Zhang et al 2013;Newhouse et al 2014).…”
Section: Enhancing Blight Resistance Through Genetic Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because decreased oxalate production in C. parasitica is associated with reduced virulence Anagnostakis 1983, 1985;Chen et al 2010), it was hypothesized that detoxifying oxalate at the canker margins would protect plant cells and enhance resistance to the blight. A natural effect of OxO is to augment host resistance, and numerous studies have shown that overexpressing OxO (i.e., producing more of the enzyme or producing it in additional tissues) in transgenic plants can enhance resistance to a variety of pathogens (Donaldson et al 2001;Liang et al 2001;Schneider et al 2002;Hu et al 2003;Livingstone et al 2005;Dong et al 2008;Walz et al 2008;Partridge-Telenko et al 2011;He et al 2013;Zhang et al 2013;Newhouse et al 2014).…”
Section: Enhancing Blight Resistance Through Genetic Transformationmentioning
confidence: 99%
“…These plants exhibit enhanced resistance to C. parasitica (Zhang et al 2013;Newhouse et al 2014) (Fig. 3).…”
Section: Enhancing Blight Resistance Through Genetic Transformationmentioning
confidence: 99%
“…As an example of the latter, the phytotoxin oxalic acid is central to pathogenicity of Cryphonectria parasitica, the cause of catastrophic epidemics of chestnut blight [102]. Significantly less disease development was observed in American chestnut trees transformed with a wheat gene coding for the production of the degradative enzyme, oxalate oxidase [103]. As another example, a toxin-degrading enzyme encoded by a barley gene was transformed into wheat, resulting in resistance in the wheat to the highly destructive disease, Fusarium head blight [104].…”
Section: Detoxifying Pathogen Toxinsmentioning
confidence: 99%
“…In addition to the promising carbon sequestration, the chestnut has the ability to provide consistent nutrition for wildlife and livestock, as well as timber for humans [3, 4, 11]. Because of the American Chestnut's dominance, the decline of this tree is devastating for both the ecosystem and economics, and the tree currently survives an understory shrub which rarely flowers [1, 2, 12, 13]…”
Section: Introductionmentioning
confidence: 99%
“…was first documented in North America in 1905 at the New York Zoological Garden by H.W. Merkel [2, 14]. In a time span of 50 years, this fungus led to the near eradication of the American Chestnut [2, 4, 15, 16].…”
Section: Introductionmentioning
confidence: 99%